Roman Africa on screen: an exotic otherness - Aguado Cantabrana, Oskar (Ex Novo: Journal of Archaeology, 2025)
This article analyses the reception of the African territory in a limited number of films and series set in ancient Rome and produced at different historical moments. In the first section, it deals with the image of Carthaginian Africa in two Italian films from the early 20th century: Cabiria (1914) and Scipione l'Africano (1937). The second section analyses the image of Roman Africa in three more recent US productions: Gladiator (2000), Ben-Hur (2016) and Those About to Die (2024). This study delves into certain war-political conditioning factors and some contemporary socio-cultural trends, specific to each period of production, which may have influenced the audiovisual representation of North African territories in pre-Roman and Roman times. In this vein, I will identify some of the most recurrent stereotypes about the “African” or the “Oriental” in these productions, in relation to relevant historical issues such as colonialism, nationalism, orientalist visions, slavery –ancient and modern– and racism.